THE CHARACTER EDUCATION BASED ON THE LOCAL WISDOM OF PIIL PESENGGIRI LAMPUNG - Ulfah, Ulfah Umurohmi; Maisaroh, Iis (Al-Ibda: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Abstract This study explores the integration of Lampung's local wisdom, Piil Pesenggiri, into character education for students in madrasahs, aiming to understand how these cultural values contribute to developing education that meets contemporary challenges. It underscores the necessity of strengthening individual character and preserving local wisdom, enhancing both cultural identity and societal cohesion. By examining Piil Pesenggiri's principles—emphasizing dignity, self-reliance, religious values, communal support, and tolerance—the research seeks to offer significant contributions to character education and cultural preservation amidst modernization and globalization.